Tribunais de Contas e o controle fiscal das contas públicas: um estudo sistêmico autorreferencial no âmbito do Estado do Pará - PANTOJA, Fernanda Pinheiro (Universidade Federal do Pará, 2024)
In the face of the complex panorama of oversight and control of public accounts, this research sought an innovative and systemic knowledge approach concerning Audits Courts as organizations, particularly focusing on their performance as well as their intra and inter- institutional communication. While, on the one hand, academic production admits the centennial importance of these public bodies in public administration oversight, highlighting them as essential for the quality of democracy, on the other hand, there are also studies showing ambiguities between what these bodies do and what they are supposed to do. Thus, from the perspective of the General Theory of Social or Self-Referential Systems, which acknowledges the relevance and uniqueness of communications in understanding social phenomena, the functioning of these organizations was examined. To this end, a heuristic research was conducted with hypothesis formulation, aiming to analyze the informational flows established between the TCE-PA (Audit Court of the State of Pará) as an organizational system and the political-administrative system of Pará (including the Executive Power and the Parliament), regarding the control and oversight of governmental fiscal management and their respective effects on public accounts management practices. This is an exploratory-descriptive study of a qualitative nature, whose data collection included bibliographic and documentary research, complemented by semi-structured interviews conducted with one-third of the deliberative body of the institution in question. Subsequently, the data were subjected to content analysis techniques. The research, in the examined, based on the choices and distinctions carried out during the observation process, resulted in an explanatory scheme of this communicational dynamic. The main results highlight that: the autopoietic process of the TCE-PA as an organizational system stems from interactions between norms, procedures, and decisions taken, which continuously reproduce and update its operations and institutional functions. This not only underscores the uniqueness of the entity in question but also reveals, in light of the systemic interpenetration process, its capacity for mobilization and connection with different organizations, as it operates in distinct functional systems. The information and messages produced and issued by TCE-PA, within the scope of its constitutional and legal competencies, reverberate in the public accounts management practices in Pará, albeit asymmetrically, considering, among other factors, the different and divergent aspects involved in the conception of normative rules, regulatory guidelines, and procedures that guide fiscal control in the country.